Only low intensity of aerobic exercise improves respiratory compliance in pulmonary hypertensive rats - Rigatto, Katya; SG Bós, Denielli Da; Fernandes, Renata; Jaenisch, Rodrigo B; Lago, Pedro Dal (Journal of Cardiology and Cardiovascular Medicine, 2019)
Objective: To investigate in an animal model of Pulmonary Hypertension (PH) by monocrotaline whether a lower exercise intensity, which has lower potential to provoke dyspnea symptoms, could prevent the increase the right ventricle pressure and the decrease in respiratory compliance. Setting: A research laboratory. ANIMALS: twenty-one Wistar rats were randomized to the groups: Control (CO; saline solution); PH-sedentary; PH-low and PH-moderate intensity of exercise training (ET). Interventions: They received a single saline or monocrotaline subcutaneous injection (50 mg/kg). The exercise program was performed during 3-weeks. Main Outcome Measures: Rats were evaluated by their morphometric and hemodynamic changes and by the respiratory mechanic responses induced by the exercise protocols. Results: Both protocols of ET significantly (p < 0.05) attenuated the increase in the right ventricular systolic pressure. However, the lower intensity was more effective to prevent the impairment in the respiratory and quasi-static compliance. Conclusion: Collectively, our results showed for the first time the benefits of ET to the respiratory system mechanics. We also demonstrated that intensity is crucial in PH, probably due to the difficulty to match VO2 capacity and O2 demand during exercise. The improvement in quasi-static compliance not only might improve the ability to breathe, and capture oxygen, but also welfare.